Patients presenting with depression to a psychiatry clinic:a descriptive survey - Thilini Rajapakse; Abeera Sivapalasingam (Sri Lanka Journal of Psychiatry, 2011)
Clinical experience suggests that depression is common in Sri Lanka. This study aims to describe the characteristics of patients with depressive symptoms presenting to a psychiatry clinic at a teaching hospital in central Sri Lanka, over a period of one year. Information was collected retrospectively, based on clinic notes. Relatively older patients (mean age 41 years), female patients (65.3%) and those with a recent history of attempted self harm (28.5%) were common. Attempted self-poisoning was the commonest method of attempted self harm. Patients with co-morbid alcohol use disorders (5.6%), and those with prominent symptoms of somatisation (31.2%), were less than expected.